Pharmacokinetics of linezolid in septic patients with and without extended dialysis - Swoboda, Stefanie; Ober, Michael; Lichtenstern, Christoph; Saleh, Soundos; Schwenger, Vedat; Sonntag, Hans-Günther; Haefeli, Walter E.; Hempel, Georg; Hoppe-Tichy, Torsten; Weigand, Markus A. (European journal of clinical pharmacology, 2010)
Linezolid is an option for the treatment of infections caused by multiresistant Gram-positive bacteria. The survival of critically ill patients with acute renal failure (ARF) can be improved by increasing the dose of renal replacement therapy. Extended (daily) dialysis (ED) is a new and important approach to renal replacement therapy in intensive care units. The aim of the study was to evaluate the pharmacokinetics of linezolid in septic patients without ED and on ED, respectively.